2014
DOI: 10.3892/ijo.2014.2510
|View full text |Cite
|
Sign up to set email alerts
|

Sine oculis homeobox homolog 1 promotes DNA replication and cell proliferation in cervical cancer

Abstract: Abstract. Malignant proliferation is the fundamental trait of tumor cells. The initiation of DNA replication represents a key process for cell proliferation, and has a marked impact on tumorigenesis and progression. Here we report that Sine oculis homeobox homolog 1 (SIX1) functions as a master regulator in DNA replication of cervical cancer cells. The expression of SIX1 was induced by the E7 oncoprotein of human papillomaviruses in cervical intraepithelial neoplasia and cervical cancer. The increase of SIX1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…Increased SIX1 expression resulted in the upregulation of multiple genes related to the initiation of DNA replication. This previous report contained various structural and functional components that represented targets for antineoplastic agents . Such results imply the nuclear matrix, which is the site of many nuclear functions including transcription, replication, the formation of chromatin loops and the control of DNA supercoiling, may be a potential target for cancer therapy …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased SIX1 expression resulted in the upregulation of multiple genes related to the initiation of DNA replication. This previous report contained various structural and functional components that represented targets for antineoplastic agents . Such results imply the nuclear matrix, which is the site of many nuclear functions including transcription, replication, the formation of chromatin loops and the control of DNA supercoiling, may be a potential target for cancer therapy …”
Section: Discussionmentioning
confidence: 99%
“…A similar study also found that Sine oculis homeobox homolog 1 (SIX1) functions as a master regulator in the DNA replication of cervical cancer cells. 38 Increased SIX1 expression resulted in the upregulation of multiple genes related to the initiation of DNA replication. This previous report contained various structural and functional components that represented targets for antineoplastic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this finding, we can speculate that the transcriptional regulation of the identified cell cycle genes could depend on the interplay between MYC, MINCR, and one of the members of the Six family of transcription factors. Interestingly, the Six1 protein has recently been found to promote DNA replication and cell proliferation in cervical cancer by regulating the expression of multiple genes related to the initiation of DNA replication (62).…”
Section: Discussionmentioning
confidence: 99%
“…Formalin-fixed, paraffin-embedded tissue blocks were retrieved from the archive and were analyzed by IHC described previously [21]. In short, The Avidin-Biotin Complex (ABC) Vectastain Kit (Zsgb-Bio, Beijing, China) was used and the DOT1L polyclonal antibody (1:250; ab64077; Abcam), H3K79me2 polyclonal antibody (1:200; ab3594; Abcam), cyclin D3 antibody (1:100; ab63535; Abcam), and the CDK6 polyclonal antibody (1:500; GTX103992; GeneTex) were used as primary antibodies incubated with tissue sections (2 mm) after heat-induced epitope retrieval (10 mM sodium citrate buffer of pH 6.0), followed by incubation with a secondary antibody conjugated to peroxidase (1:100; Dako).…”
Section: Methodsmentioning
confidence: 99%